NEGARA DAN PETANI (STUDI KASUS PEMIHAKAN PEMERINTAH KABUPATEN INDRAGIRI HILIR TERHADAP PETANI KELAPA) - Satria, Kiki; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study used a qualitative descriptive method. Location Research in Indragiri Hilir the focus of research in the Department of Plantation Indragiri Hilir.Plantation sector is one of the backbone of the economy Indragiri Hilir. Various plantation crops that have been developed over the years is the local coconut, hybrid coconut, oil palm, rubber, coffee, chocolate and nut. Of various commodities, the local oil is excellent. Plantation yield potential in the downstream Indragiri oil production reached 390,924.28 tons per year with a land area of 295,380.24 hectares. With this potential makes Indragiri Hilir listed as one of the world's largest oil region, even dubbed as the "Land of Coconut Overlay World". Potential land for plantation commodity development is an area of 722 806 ha. And has been used about 600 691 ha. As State palm plantation owners largest in the world, Indonesia has a plantation area of 3,7juta acres scattered palm islands. Kateman or more regions known as blunt River is the District which has the most extensive coconut plantations there. The gardens are owned by PT. Pulau Sambu, an agribusiness company that has a garden at the same time in the palm oil mill Indragiri Hilir.Though coconut plantations (copra) in Inhil well managed by the planters, but the marketing of palm fluctuate so that the bargaining position of farmers is very low in determining the price, because they depend on the purchase by the company. This is because far too Regency Inhil give freedom to companies engaged in the coconut to make your own garden, for the supply of industrial raw materials. So when the company has been able to 'self' with their crops as a raw material, they will suppress the purchase price of coconut farmers. As a result of this monopoly in the market price of oil becomes unstable, even often substandard. This is due to lack of impartiality Government Indragiri Hilir so that the lives of farmers in Indragiri Hilir was not improved.